2021
DOI: 10.3389/fvets.2021.552350
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Modifiable Exposures and Their Association With Owner Reported Inflammatory Bowel Disease Symptoms in Adult Dogs

Abstract: Background: Inflammatory bowel disease (IBD) is an idiopathic multifactorial disease in humans and dogs, usually assigned to the interactions between genes, gut microbiota, diet, environment, and the immune system. We aimed to investigate the modifiable early life exposures associated with IBD in dogs.Materials and Methods: The study data was extracted from the validated owner-reported DogRisk food frequency questionnaire. This was a cross-sectional questionnaire-based study that tested 21 different early life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 77 publications
(96 reference statements)
3
12
0
Order By: Relevance
“…A similar study also found that previous parvovirus enteritis was a risk factor for persistent gastrointestinal signs, and among dogs that had recovered from parvovirus infection, markers of disease severity were associated with that risk (133). In another study, early modifiable risk factors for CE in adulthood included vaccination of the dam during pregnancy, type of solid food fed to puppies during the first 6 months, and the puppy's body condition ("slim" rather than "normal weight") (134). These results should be interpreted with caution because of methodological limitations such as retrospective owner questionnaires, participant bias and broad diet types that were not nutritionally controlled.…”
Section: Early-life Risk Factors For Chronic Enteropathy In Adult Dogsmentioning
confidence: 99%
“…A similar study also found that previous parvovirus enteritis was a risk factor for persistent gastrointestinal signs, and among dogs that had recovered from parvovirus infection, markers of disease severity were associated with that risk (133). In another study, early modifiable risk factors for CE in adulthood included vaccination of the dam during pregnancy, type of solid food fed to puppies during the first 6 months, and the puppy's body condition ("slim" rather than "normal weight") (134). These results should be interpreted with caution because of methodological limitations such as retrospective owner questionnaires, participant bias and broad diet types that were not nutritionally controlled.…”
Section: Early-life Risk Factors For Chronic Enteropathy In Adult Dogsmentioning
confidence: 99%
“…Furthermore, diet has also been shown to impact mucosal microbiota and the GI metabolome and mucosal microbiota in dogs with cIBD (Atherly et al, 2019;Ambrosini et al, 2020a). Recently, early-life risk factors for developing IBD have been an area of interest and studies have identified similar findings in dogs and humans with cIBD/IBD such as an association with early life high-fat low-carbohydrate diets and the later development of IBD/cIBD (Hemida et al, 2021). Like humans, a diagnosis of cIBD is made based on chronic GI signs, eliminating other known causes of intestinal inflammation and histopathologic confirmation of intestinal inflammation.…”
Section: A One Health Approach To Improving Treatment For Ibd-in Human and Canine Patientsmentioning
confidence: 99%
“…In veterinary medicine, the use of the term chronic enteropathies (CE) is preferred instead of IBD to identify a group of idiopathic intestinal disorders with evident GI signs (recurrent or chronic), and inflammation in the lamina propria of the small intestine, large intestine, or both [ 5 ]. Nonetheless, several phenotypes of IBD have been identified in dogs [ 6 ]. In fact, IBD in dogs has different forms when compared to humans, where more standardized clinical, endoscopic, and pathologic aspects can be found [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%